Evaluating the Impact of Education on Pharmacist Tobramycin Dose Recommendations for Cystic Fibrosis and a Review of Perceptions on Pharmacist-Led Charting. (December 2022) - Le, Tran; Lord, Louise; Pignataro, Silvana; Simioni, Diana; Cheah, Ron
Background: Pharmacists routinely interpret and optimize tobramycin dosing for people with cystic fibrosis (PwCF). Objectives: To determine the impact of tobramycin therapeutic drug monitoring (TDM) education on pharmacist dose recommendations, and to explore nurses' and medical doctors' perceptions toward pharmacist-led TDM charting. Methods: This study involved 3 phases: a 12-month retrospective audit of PwCF prescribed tobramycin to identify the appropriateness of pharmacists' dose recommendations, a pharmacist tobramycin educational intervention utilizing a voiceover presentation with pre- and post-online tobramycin TDM assessment (involving multiple choice pharmacokinetics and case-based scenario questions), and a cross-sectional survey of respiratory nurses' and doctors' perceptions toward pharmacist-led TDM charting. The pharmacists' dose recommendations, in the audit and case-based questions, were considered appropriate if subsequent levels achieved the targeted area under the curve (AUC). Results: Audit results revealed that 44.4% of the 277 pharmacist dose recommendations identified were appropriate. The pre- and post-interventional assessments were completed by 51 and 52 pharmacists, respectively. Post intervention, correct scores were significantly higher than pre-intervention, evident in both the pharmacokinetics (median score 75% vs 100%; P = 0.048) and case-based scenario (median score 60% vs 90%; P < 0.0001) questions. Of the 54 nurses and medical doctors surveyed, 92.6% supported the implementation of pharmacist-led tobramycin charting. Conclusion: The study demonstrated an increased accuracy and appropriateness of pharmacists' tobramycin pharmacokinetics knowledge and TDM dose recommendations post-educational intervention and highlighted nurses' and medical doctors' support of pharmacist-led tobramycin TDM charting.